2013
DOI: 10.1371/journal.pone.0074488
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Melanocyte Stimulating Hormone (α-MSH) Is a Post-Caspase Suppressor of Apoptosis in RAW 264.7 Macrophages

Abstract: The neuropeptide alpha-melanocyte stimulating hormone (α-MSH) is an important regulator of immune cell activity within the immunosuppressive ocular microenvironment. Its constitutive presence not only suppresses macrophage inflammatory activity, it also participates in retinal pigment epithelial cell (RPE) mediated activation of macrophages to function similar to myeloid suppressor cells. In addition, α-MSH promotes survival of the alternatively activated macrophages where without α-MSH RPE induce apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It was also demonstrated that mouse RPE cells could activate macrophages to function similar to myeloid suppressor cells. This effect was mediated by alpha-melanocyte-stimulating hormone as an immunosuppressive regulator ( Taylor, 2013 ). Similarly, the mechanism of immunomodulaton by hESC-RPE cells may be complex and may involve regulation of various immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that mouse RPE cells could activate macrophages to function similar to myeloid suppressor cells. This effect was mediated by alpha-melanocyte-stimulating hormone as an immunosuppressive regulator ( Taylor, 2013 ). Similarly, the mechanism of immunomodulaton by hESC-RPE cells may be complex and may involve regulation of various immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…This has suggested that the RPE produce a pro-apoptotic signal in macrophages that is countered by α-MSH. The apoptotic signal blocked by α-MSH, or how α-MSH blocks apoptosis is not yet understood [20]. In parallel, the ARPE-19 conditioned media depleted of α-MSH and NPY were significantly diminished in their capacity to suppress activation of the phagolysosome in macrophages, and the macrophages treated with the depleted conditioned media are appearing to be dying.…”
Section: Discussionmentioning
confidence: 99%
“…In murine primary macrophages, the MCR agonist AP124 promotes phagocytosis of zymosan particles and of apoptotic neutrophils acting mainly through MC3R [78]. However, treatment of RAW 264.7 cells with α -MSH reduces phagocytosis of apoptotic cells [79] and E. coli bioparticles, and when combined with NPY it also reduces phagocytosis of gram-positive bioparticles [80]. Our group found that treatment of primary rat microglia with NDP-MSH does not affect basal or LPS-induced phagocytosis of latex beads; however, NDP-MSH inhibits phagocytosis induced by the TLR2 agonist Pam 3 CSK 4 in microglial cells [49].…”
Section: Pomc-derived Peptidesmentioning
confidence: 99%